# How do you find the sum of #Sigma (3i-1)# from i=1 to 6?

57

By signing up, you agree to our Terms of Service and Privacy Policy

To find the sum of Σ(3i - 1) from i = 1 to 6, you can use the formula for the sum of an arithmetic series. The formula is:

Sum = n/2 * (first term + last term)

In this case: First term = 3(1) - 1 = 2 Last term = 3(6) - 1 = 17 Number of terms (n) = 6

Plug these values into the formula: Sum = 6/2 * (2 + 17) = 3 * 19 = 57

So, the sum of Σ(3i - 1) from i = 1 to 6 is 57.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7